Effect of torrefaction on the properties of briquettes produced from agricultural waste - Granado, Marcos Paulo Patta [UNESP]; Gadelha, Antonia Mabrysa Torres; Rodrigues, Deyvison Souza; Antonio, Graziella Colato; De Conti, Andrea Cressoni (Elsevier, 2023)
In this study, briquettes produced from cassava rhizome, sugarcane bagasse and straw were torrefied at 250 °C for 90 min to verify the effects of the process on their structure and properties such as density, durability, energy content, and energy density. The briquettes had a relaxed density of 1270 kg/m3 for those produced from cassava rhizome, 1240 kg/m3 from sugarcane bagasse, and 1300 kg/m3 from sugarcane straw. The torrefaction procedure increased calorific value of the briquettes by 9–13-fold. However, changes in briquette strength were identified after torrefaction, with a longitudinal deformation of 12.9–26.6 % and cracks in its bodies. Consequently, fragments were produced after durability testing. Moreover, briquette density decreased by 36 % for cassava rhizome, 50 % for sugarcane bagasse, and 55 % for sugarcane straw. The produced cassava rhizome briquettes exhibited the highest energy yield when torrefied. Combining these technologies facilitates the use of residues from agriculture for energy generation.
Keywords: Biomass feedstock; Durability; Energy density; Solid biofuel; Strength; Upgrading technologies